Dekontaminasi Mycobacterium avium subspecies paratuberculosis pada feses menggunakan beberapa jenis desinfektan - Ika Suharti; Ni Luh Putu Ika Mayasari; Fachriyan Hasmi Pasaribu (Jurnal Sain Veteriner, 2018)
Paratuberculosis or Johne’s Disease is a granulomatous enteritis chronic disease of domestic and wild ruminants caused by infection of Mycobacterium avium subspecies paratuberculosis. The disease commonly infects dairy cattle with clinical signs of chronic diarrhea, decreasing body weight, low milk production, oedema, anemia and occasionally infertility. The basic procedure in order to control Paratuberculosis in farms is to do a good and proper handling of animal faecal. Disinfection of animal environments such as pens, faecal, sewerage and sewage are important in prevention of transmission of this disease. The purpose of this research is to determine specific disinfectan and dosage for Mycobacterium avium subspecies paratuberculosis decontamination in cattle feces so  it can be applied as disease control measures. Cow's feces were contaminated with MAP 105CFU/ml and treated with ammonium quartener, phenolic and formaldehyde disinfectant doses 10%, 15% and 20%. The effectiveness of the disinfectant was tested based on MAP identification using Löwenstein-Jensen culture medium and nested Polymere Chain Reaction(PCR). The results showed 15% and 20% doses of formaldehyde disinfectants efective to decontaminate Mycobacterium avium subspecies paratuberculosis  in catle feces.